Cider and dessert apples: What is the difference?. Issue 6 (22nd June 2022) - Soomro, Tayab; Watts, Sophie; Migicovsky, Zoë; Myles, Sean
Societal Impact Statement: Apples are among the most widely consumed fruits in the world, with a third of all apples being pressed into apple juice or fermented into cider. Cider has grown in popularity in Canada and the United States, and North American cider makers are increasingly interested in using traditional European 'cider apples' rather than using commonly grown 'dessert apples' that are grown primarily for fresh consumption. While we find that commonly grown dessert apples do differ from European cider apples for a small number of cider making characteristics, our results show that dessert apples are most often indistinguishable from cider apples across 10 traits. Our work provides a first step towards quantifying the differences between these two apple types. Abstract : Apples are among the most widely consumed fruits in the world, with a third of all apples being pressed into apple juice or fermented into cider. Cider has grown in popularity in Canada and the United States, and North American cider makers are increasingly interested in using traditional European 'cider apples' rather than using commonly grown 'dessert apples' that are grown primarily for fresh consumption. While we find that commonly grown dessert apples do differ from European cider apples for a small number of cider making characteristics, our results show that dessert apples are most often indistinguishable from cider apples across 10 traits. Our work provides a first step towards quantifying the differences between these two apple types.